Relationship Between Leadership Style And Motivation With Nurse Performance In Hospitals - Annisa Aulia Rakhim; Syamsul Arifin; Achmad Rofi'i (Interest : Jurnal Ilmu Kesehatan, 2021)
Background: Performance is the quantity and quality of task achievement. Good leadership can motivate employees to improve performance. This study aims to determine the relationship between leadership style and motivation on the performance of nurses in hospitals. Methods: This study is a systematic review and meta-analysis. Article searches were carried out using search engines, including Google Scholar, PubMed, Sciendirect, BMJ, and Garuda Portal. The keywords used were “leadership style” OR motivation AND performance AND nurses AND “cross-sectional”, performance AND nurses. Determination of the eligibility of articles using PRISMA. Results from the entire literature were selected using inclusion and exclusion criteria. Measurement of effect size using RevMan 5.3 program. Results: All research obtained using a cross sectional research design. Good leadership style increased nurse performance by 3.19 times compared to poor leadership style and was statistically significant (OR= 3.19; 95% CI= 1.76 to 5.79; p<0.001). The sample of leadership style variables is 1290 nurses. Good motivation can improve nurse performance by 3.65 times compared to poor motivation and is statistically significant (OR= 3.65; 95% CI= 1.95 to 6.82; p< 0.001). Conclusion: Leadership style and motivation as factors in improving nurse performance. The leadership style of the head must be adapted to the needs of each room and must be flexible. With the right leadership style, nursing services in the room can be aligned with hospital goals.